2019
DOI: 10.1007/s00383-019-04570-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term feeding issue and its impact on the daily life of congenital diaphragmatic hernia survivors: results of the first patient-led survey

Abstract: Background CDH UK is a registered charity governed by a volunteer committee and providing informal support to patients, families and healthcare workers affected directly or indirectly with congenital diaphragmatic hernia (CDH) internationally. This is the first patient-led survey undertaken by CDH UK aiming for highlighting the feeding problems and their impact on the daily life of CDH survivors. Methods Answers from CDH survivors were collected through an online questionnaire (SurveyMonkey ® ) undertaken by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In general, a higher prevalence of GER was detected after evaluation with impedance and pH metry [ 13 ]. In a patient-led survey by CDH UK, a registered charity for CDH patients governed by a volunteer committee, 62–92% of 151 participants reported GER symptoms [ 25 ]. Interestingly, “three fourths of the responders did not agree with the statement that feeding problems improved with time”.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a higher prevalence of GER was detected after evaluation with impedance and pH metry [ 13 ]. In a patient-led survey by CDH UK, a registered charity for CDH patients governed by a volunteer committee, 62–92% of 151 participants reported GER symptoms [ 25 ]. Interestingly, “three fourths of the responders did not agree with the statement that feeding problems improved with time”.…”
Section: Discussionmentioning
confidence: 99%
“… Up to 75% of surviving CDH infants have feeding problems like gastro‐esophageal reflux disease, need for tube feeding, oral aversion 65 . Approximately one in five CDH newborns are discharged on partial tube feeding 66 (Figure 3).…”
Section: Childhood Morbiditymentioning
confidence: 99%
“…[5][6][7] However, the predictive value of these parameters for (co) morbidity in surviving CDH infants, for example, pulmonary hypertension (PH), gastrointestinal morbidities, or prediction of the actual (postnatal) defect size remains limited. 3,4,[8][9][10][11] Previous studies have explored the predictive value of the prenatal stomach position (SP) for the occurrence of postnatal morbidity, using the grading system proposed by Cordier et al [12][13][14][15] It was shown that the prenatal SP is a potential marker for postnatal survival, the need for postnatal patch repair, need for extracorporeal membrane oxygenation (ECMO), and need for prolonged respiratory support. 12,14 Moderate to almost perfect inter-and intraobserver agreement for the determination of prenatal SP has been shown by different groups, which might support its clinical applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Currently the most validated predictive ultrasound (US) parameters for postnatal outcome in fetuses with left‐sided CDH include the observed‐to‐expected lung‐to‐head ratio (O/E LHR) and liver position (intra‐abdominal or intra thoracic) 5–7 . However, the predictive value of these parameters for (co)morbidity in surviving CDH infants, for example, pulmonary hypertension (PH), gastrointestinal morbidities, or prediction of the actual (postnatal) defect size remains limited 3,4,8–11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation